2022
DOI: 10.3390/jcdd9110368
|View full text |Cite
|
Sign up to set email alerts
|

Cardio-Ankle Vascular Index as an Arterial Stiffness Marker Improves the Prediction of Cardiovascular Events in Patients without Cardiovascular Diseases

Abstract: Several studies have reported that the cardio-ankle vascular index (CAVI), a non-invasive measurement of arterial stiffness, is associated with the incidence of cardiovascular events. We investigated whether adding CAVI to a risk score improves the prediction of cardiovascular events in the setting of primary prevention. This retrospective observational study included consecutive 554 outpatients with cardiovascular disease risk factors but without known cardiovascular disease (68 ± 9 years, 64% men). The CAVI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…26 CAVI may have higher discrimination in all-cause mortality and major adverse cardiovascular endpoints. 27 CAVI is a more stable indicator, CAVI has the advantages of non-invasive, immune to blood pressure, and inexpensive. Generally, arteriosclerosis detectors can measure CAVI and ankle brachial index(ABI), and can be considered for large-scale vascular screening in the future.…”
Section: Evaluation Of Arteriosclerosismentioning
confidence: 99%
“…26 CAVI may have higher discrimination in all-cause mortality and major adverse cardiovascular endpoints. 27 CAVI is a more stable indicator, CAVI has the advantages of non-invasive, immune to blood pressure, and inexpensive. Generally, arteriosclerosis detectors can measure CAVI and ankle brachial index(ABI), and can be considered for large-scale vascular screening in the future.…”
Section: Evaluation Of Arteriosclerosismentioning
confidence: 99%
“…The cardio–ankle vascular index (CAVI) is acknowledged as a blood pressure-independent marker of arterial stiffness across the entire arterial system, extending from the aortic root to the ankle [ 13 ]. Previous studies have reported that an abnormal CAVI value (>9.0) is associated with a significant incidence of cardiovascular events, including cardiovascular death, myocardial infarction, stroke, hospitalization for HF, and coronary revascularization [ 14 ]. Therefore, arterial stiffness and VO 2 are prognostic factors for cardiovascular disease, although the relationship between arterial stiffness and VO 2 in patients with AMI remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…A retrospective, single-center cohort study including outpatients with cardiovascular disease risk factors but without known cardiovascular disease evaluated the prognostic impact of cardio-ankle vascular index (CAVI) [ 8 ]. Importantly, results showed that CAVI improved the prediction of cardiovascular events (the addition of CAVI to a conventional risk score for coronary heart disease in Japan significantly improved the C statics from 0.642 to 0.713; p = 0.04) [ 8 ].…”
mentioning
confidence: 99%